Professional ethics and civic morals - Durkheim, Emile (Routledge classics, 2019)
Émile Durkheim is one of the founding fathers of sociology and Professional Ethics and Civic Morals is one of his most neglected yet insightful works. Durkheim's view that the instability of industrial society was connected to the decline of religion and his characterization of the state as the ultimate moral force in society reveal his lifelong engagement with the relationship between the individual and society. He also believed that education was vitally important in sustaining a moral life and was deeply involved in the campaign for educational reform in France.